Results of studies of human dirofilariasis in Russia - Sergiev, V P; Supriaga, V G; Bronshteĭn, A M; Ganushkina, L A; Rakova, V M; Morozov, E N; Fedianina, L V; Frolova, A A; Morozova, L F; Ivanova, I B; Darchenkova, N N; Zhukova, L A (Meditsinskaia parazitologiia i parazitarnye bolezni, 2014)
Human dirofilariasis is a pressing health problem in Russia. By 2014, there have been as many as 850 Dirofilaria repens-infested people living in 42 subjects of the Russian Federation. One of the favorable factors for circulation and spread of invasion is a temperature of above +20-24 degrees C; when the latter is maintained during at least 20 days there may be 1.-1.5 circulations of invasion in the carrier and a 2.8-fold increase in transmission intensity. The border ofa dirofilariasis area with a temperate climate is southward to 58 degrees N in European Russia and West Siberia and southward to 50 degrees N in the Far East. The conditions in the human body have been found to be more favorable for the development of Dirofilaria than considered before and allow the helminth to achieve sexual maturity and to propagate. If man has microfilaremia, he may be a source of invasion. It is necessary to examine venous blood by the enrichment method and, if possible, polymerase chain reaction and enzyme immunoassay, which make it possible to establish a diagnosis in occult invasion and to identify a pathogen species.